Blunt cervical spine injury in adult polytrauma: incidence, injury patterns and predictors of significant ligament injury on CT. Issue 11 (November 2017) - Chilvers, G.; Janjua, U.; Choudhary, S.
Abstract : Aim: To describe the pattern of cervical spine fractures in adult major trauma and identify computed tomography (CT) parameters that can predict significant ligament injury when fractures are absent; to define the normal range for parameters used; and identify common variations due to position of cervical immobilisation in a trauma patient. Materials and methods: In this retrospective study all polytrauma patients imaged using multidetector CT over a period of 5 years were identified. Patients with cervical spine fracture and suspected ligament injury in the absence of fracture were collated based on the polytrauma CT report. Predictors of ligament injury were defined based on published historical data on plain radiographs and posterior paraspinal fat pad assessment at CT. These parameters were recorded for each study with comparison to subsequent magnetic resonance imaging (MRI) as the reference standard. Results: Significant ligament injury on MRI was detected at the craniocervical junction, when CT showed a basion dens interval of >10 mm, widened incongruous C0/C1 facet joint space of >3 mm, and widened C1/2 facet joint space of >6 mm. In the subaxial cervical spine, facet subluxation >50% and obscured posterior paraspinal fat pad were the only reliable predictors of ligament injury, as confirmed on subsequent MRI. Conclusion: When fractures are absent, signs of significant ligament injury on CT at the craniocervical junction were increased basion dens interval and widened facet joints. In the subaxial cervical spine, >50% subluxation of a facet joint and obscured posterior paraspinal fat pad are indicators of significant ligament injury. Highlights: In adult polytrauma, the commonest fracture at the craniocervical junction is type 3 dens fracture. In the subaxial cervical spine, an isolated transverse process/lamina fracture (simple lateral compression morphology) is most common. Signs of significant ligament injury in the absence of fracture, at the craniocervical junction are increased basion dens interval and widened facet joints. In the subaxial cervical spine, >50% facet joint subluxation and obscured posterior parsapinal fat pad are reliable signs of ligament injury.